2009
DOI: 10.2320/matertrans.me200823
|View full text |Cite
|
Sign up to set email alerts
|

Dealloying of Cu-Zr-Ti Bulk Metallic Glass in Hydrofluoric Acid Solution

Abstract: The dealloying behavior of Cu 60 Zr 30 Ti 10 metallic glass was investigated under free corrosion conditions using hydrofluoric acid (HF) solutions at room temperature. After immersing in HF solutions with various concentrations (0.05, 0.1, 0.5 and 1 M) for 300 s, color of all samples changed to be pinkish or peachy, which was ascribed to Cu based on the XRD patterns. According to the SEM-EDS study, HF immersion selectively leached the Zr and Ti elements, leaving Cu behind. Increasing the HF concentration incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Formation of BMGs in the Cu-rich Cu-Zr-Ti ternary system has been researched by Wang et al [10]; the BMGs on each composition line manifest decreased thermal stabilities and glass forming abilities with increasing Ti content. Dai et al [11] by Naoi et al [15] and its dealloying behavior has been analysed under free corrosion conditions [16] resulting in the idea, that dealloying metallic glasses may be a possible candidate for developing nanostructured metals. Moreover, Basu et al [17] have shown that Miedema's approach has been useful in determining the glass forming composition range for a particular alloy system (including the Cu-Zr-Ti system).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of BMGs in the Cu-rich Cu-Zr-Ti ternary system has been researched by Wang et al [10]; the BMGs on each composition line manifest decreased thermal stabilities and glass forming abilities with increasing Ti content. Dai et al [11] by Naoi et al [15] and its dealloying behavior has been analysed under free corrosion conditions [16] resulting in the idea, that dealloying metallic glasses may be a possible candidate for developing nanostructured metals. Moreover, Basu et al [17] have shown that Miedema's approach has been useful in determining the glass forming composition range for a particular alloy system (including the Cu-Zr-Ti system).…”
Section: Introductionmentioning
confidence: 99%
“…In this article we present modifications of the atomic structure of Cu 60 Zr 20 Ti 20 and Cu 55 Zr 16 Ti 29 (at. %) metallic glass upon annealing at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This process provides the finest pore size, in the nanometre range, as shown for Au-Ag [7], Au-Cu [7], Au-Sn [8], Cu-Mn [9] alloys. De-alloying of homogeneous amorphous alloys as well as of phase separated amorphous phases, has been attempted in a number of cases with success [10][11][12]. multicomponent, removal of elements bring composition outside the glass-forming range, nucleation…”
Section: Introductionmentioning
confidence: 99%
“…difference of the two sides of ribbons being either smooth and shiny or corrugated and dull, quenched-in crystals and even nuclei. Studies have recently been conducted on the dealloying behaviour of Pd 30 Ni 50 P 20 glassy ribbons by electrochemical etching [11], on free corrosion of CueZreTi bulk metal glasses in hydrofluoric acid [12] and on TieYeAleCo phase-separated glass after immersion in sulphuric acid [13] showing in all cases the depletion of the less noble elements and the formation of nanoporous structures. Dealloying was also briefly shown to be feasible in a multicomponent Au-alloy, Au 35 Si 20 Cu 28 Ag 7 Pd 5 Co 5 [11].…”
Section: Introductionmentioning
confidence: 99%